The Effectiveness of Digital vs. Analogue Teaching Resources in a Flipped Classroom for Undergraduate Focus Cardiac Ultrasound Training: A Prospective, Randomised, Controlled Single-Centre Study - Johannes Weimer; Florian Recker; Rebecca Krüger; Lukas Müller; Holger Buggenhagen; Sandra Kurz; Andreas Weimer; Liv-Annebritt Lorenz; Roman Kloeckner; Johannes Ruppert; Elias Waezsada; Sebastian Göbel; et al. (Education Sciences, 2025)
Introduction: This study investigated the effectiveness of e-learning compared to traditional teaching methods in ultrasound education, centring on a focus cardiac ultrasound (FoCUS) course for third-year undergraduate medical students. With the rise of digital teaching methods, it is essential to evaluate their impact on the development of theoretical and practical skills in ultrasound training. Methods: A prospective, randomised, controlled trial was conducted involving two groups of students participating in a one-day FoCUS course delivered in a flipped classroom format. The study group used e-learning resources, while the control group used hard-copy lecture notes. Assessments were conducted at three stages: before the course, during the preparation phase, and after the course. Evaluations included self-assessment surveys, theory tests, and practical exams using direct observation of procedural skills (DOPS) tests. The study group had 15% less practice time compared to the control group. Results: A total of 109 complete datasets (study group, n = 52; control group, n = 57) were analysed. Both groups showed an equivalent initial level of and a continuous and significant (p < 0.01) increase in subjective and objective skills over the evaluated time frame. The study group achieved significantly (p = 0.03) higher results in DOPS (T2) than the control group. No significant differences were found in the total scores of the theory tests (T2 + T3) or DOPS (T3). Both groups rated their teaching materials, motivation, and the course concept in similarly high scale ranges. Conclusions: The findings suggest that e-learning is as effective as traditional methods in developing ultrasound skills and may serve as a viable alternative, even with reduced face-to-face interaction. These results indicate that accreditation processes could be applied similarly to those for traditional formats without requiring in-person training as a prerequisite for quality